Changes in liver ganglioside metabolism in obstructive cholestasis - the role of oxidative stress - Šmíd, Václav; Petr, Tomáš; Váňová, Kateřina; Jašprová, Jana; Šuk, Jakub; Vítek, Libor; Šmíd, František; Muchová, Lucie (Folia biologica (Praha), 2016)
Bile acids have been implicated in cholestatic liver damage, primarily due to their detergent effect on membranes and induction of oxidative stress. Gangliosides can counteract these harmful effects by increasing the rigidity of the cytoplasmic membrane. Induction of haem oxygenase (HMOX) has been shown to protect the liver from increased oxidative stress. The aim of this study was to determine the changes in the synthesis and distribution of liver gangliosides following bile duct ligation (BDL), and to assess the effects of HMOX both on cholestatic liver injury and ganglioside metabolism. Compared to controls, BDL resulted in a significant increase in total as well as complex gangliosides and mRNA expression of corresponding glycosyltransferases ST3GalV, ST8SiaI and B3GalTIV. A marked shift of GM1 ganglioside from the intracellular compartment to the cytoplasmic membrane was observed following BDL. Induction of oxidative stress by HMOX inhibition resulted in a further increase of these changes, while HMOX induction prevented this effect. Compared to BDL alone, HMOX inhibition in combination with BDL significantly increased the amount of bile infarcts, while HMOX activation decreased ductular proliferation. We have demonstrated that cholestasis is accompanied by significant changes in the distribution and synthesis of liver gangliosides. HMOX induction results in attenuation of the cholestatic pattern of liver gangliosides, while HMOX inhibition leads to the opposite effect.
Keywords: Gangliosides; Ligation; játra; Oxidative Stress; Bile Ducts; velikost orgánu; intracelulární membrány; oxidační stres; messenger RNA; Female; ligace; N-Acetylneuraminic Acid; Biomarkers; zvířata; proliferace buněk; gangliosidy; potkani Wistar; Cholestasis; žlučové cesty; Intracellular Membranes; RNA, Messenger; biologické markery; ženské pohlaví; Liver; Rats, Wistar; Cell Proliferation; Cytoplasm; hemová oxygenasa (decyklizující); Heme Oxygenase (Decyclizing); cytoplazma; Body Weight; Animals; kyselina N-acetylneuraminová; Organ Size; tělesná hmotnost; cholestáza